2004
DOI: 10.2527/2004.8251419x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental rumen-protected conjugated linoleic acid or corn oil on fatty acid composition of adipose tissues in beef cattle1

Abstract: Thirty-six Angus x Hereford heifers (365 +/- 60 kg) were used to determine the effects of supplemental dietary lipid sources on fatty acid composition of i.m., perianal (p.a.), and s.c. lipid depots. Lipid was supplied to diets as either corn oil or a rumen-protected conjugated linoleic acid (CLA) salt for two specific treatment periods of either the final 32 or 60 d on feed. Following an initial 56-d feeding period, heifers were fed one of three dietary treatments (DM basis): 1) basal diet containing 88% conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
5
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 33 publications
(46 reference statements)
8
52
5
1
Order By: Relevance
“…Gillis et al (2004) reported lower concentration of monounsaturated fatty acids in the meat from calves fed lipid-rich diets. There Regarding the sensorial analysis (Table 5), it is verified that the cottonseed addition over 34.09 kg for every 100 kg of the diet (P<0.05) resulted in slightly more intense strange flavor.…”
Section: Resultsmentioning
confidence: 99%
“…Gillis et al (2004) reported lower concentration of monounsaturated fatty acids in the meat from calves fed lipid-rich diets. There Regarding the sensorial analysis (Table 5), it is verified that the cottonseed addition over 34.09 kg for every 100 kg of the diet (P<0.05) resulted in slightly more intense strange flavor.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are also experiments that report a negative effect of CLA mixtures on adipogenesis, as measured by the expression levels of PPARγ and C/EBPα and the activity of glycerol-3-phosphate dehydrogenase [Griswold et al, 2003]. It is noteworthy that the isomer composition of the CLA added in these and other experiments [Evans et al, 2000;Gillis et al, 2004] was not identified, which could account for the conflicting results.…”
Section: Discussionmentioning
confidence: 50%
“…Gillis et al (2004) reported that over 86% of the CLA c-9,t-11 in beef tissue originated from the desaturation of 18:1t-11, based on duodenal flows of 18:1t-11 and CLA c-9,t-11 found within adipose tissue. Presently, there was a similar pattern between the concentration of 18:1t-11 and CLA c-9,t-11 in the muscles, although this was not always statistically evident.…”
Section: Total Lipidsmentioning
confidence: 99%